Diffuse alveolar hemorrhage in infants: Report of five cases - E. Gkogkou; I. Broux; C. Kempeneers; H. Boboli; R. Viellevoye; A. Janssen; M.-C. Seghaye; M. Mastouri (Respiratory Medicine Case Reports, 2020)
Diffuse alveolar hemorrhage (DAH) is a rare life-threatening condition in children. In this entity, the bleeding originates from the pulmonary microvasculature as a result of microvascular damage leading to blood leakage into the alveolar spaces. DAH can occur as an isolated medical entity or may be associated with other organ system injury or dysfunction. The classic triad of symptoms includes hemoptysis, anemia and diffuse pulmonary infiltrates. Hemoptysis is the usual presenting symptom but is not constant. A variety of diseases is associated with the development of DAH. Current classification organize the etiologies of diffuse alveolar hemorrhage based on the presence of severe immune disorders (such as systemic vasculitis and collagenosis) or non-immunodeficiency disorders (with an identified cardiac or non-cardiac origin, or idiopathic).The five cases of DAH presented in this study were all diagnosed in full-term infants, four males and one female, with normal neonatal adaptation and without family history of notable diseases. In all cases the diagnosis was made between the age of three and eighteen weeks-old. Moreover, all five patients, at the time of diagnosis, presented with hemoptysis, mild or severe dyspnea, anemia and abnormal chest X-rays. Consequently, the diagnosis of DAH was strongly suspected and, eventually, confirmed by bronchoscopy. Additional laboratory tests, as well as selected serologic and radiographic studies were performed in order to identify a specific etiology. The final diagnoses reflect a variety of causes: infections, idiopathic pulmonary hemosiderosis, accidental suffocation and Heiner syndrome. Treatment included oral corticosteroids except from one patient that received antimicrobial therapy.